Korelasi Jumlah Trombosit dengan Kadar Albumin pada Penderita Demam Berdarah Dengue (DBD) di Kota Mataram - Rizani, Ulfiya; Lalu Srigede; Ariami, Pancawati; Kristinawati, Erna (Journal of Indonesia Laboratory Students (JILTS), 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus. DHF can cause two main pathological changes, namely increased capillary permeability, which causes hemoconcentration due to a decrease in plasma volume in the blood vessels and hemostasis disorders caused by coagulopathy, vasculopathy and thrombocytopenia. Routine examination parameters for dengue sufferers are complete blood to monitor platelet counts. Supporting examinations are also required, one of which is checking albumin levels. This research aims to know of determine the correlation between platelet counts and levels in dengue fever sufferers in Mataram City. This research uses the Observational Analytical method with a cross sectional approach. DHF sufferers will have a complete blood count and albumin examination, then an analysis will be carried out using the Spearman test. This study used 24 samples and it was found that the overall average platelet count was 56,000/ul of blood. The platelet value was obtained with a range of 26,000/ul blood to 91,000/ul blood. The overall average albumin level is 3.28 g/dL, with a range of albumin levels from 2.78 g/dL to 4.12 g/dL. There is a relationship between platelet count and albumin levels in dengue fever sufferers in Mataram City based on the results of the Spearman test with a p value <0.05.